ANALISIS STRATEGI PEMBINAAN KESEHATAN MENTAL OLEH GURU PENGASUH SEKOLAH BERASRAMA DI ACEH BESAR PADA MASA PANDEMI - Faisal Anwar; Putry Julia (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2021)
This study aims to: analyze teachers' understanding of mental health?, know the ability of teachers to design activities to foster the health of students in dormitories?, know the process of health activities carried out by teachers in fostering mental health?, find out how teachers train mental health coaching? , What are the factors that can support and hinder the implementation of mental health coaching for students in dormitories? What are the efforts made by teachers in overcoming obstacles in carrying out mental health coaching? This study uses a qualitative descriptive method with the research subjects of caregivers from 5 Islamic boarding schools in Aceh Besar. Data were collected by observation and interviews. Triangulation was carried out through focus group discussions between researchers and caregivers. The results of the study indicate that conceptually the teacher understands the notion of mental health even though it is not fully defined by the existing definition. This study also revealed that teachers were unable to arrange mental health coaching programs because they did not have similar backgrounds.